Feasibility of Oxaliplatin, Leucovorin, and 5-Fluorouracil (FOLFOX-4) Chemotherapy in Heavily Pretreated Patients with Recurrent Epithelial Ovarian Cancer - Lee, Hee Jun (Korean Cancer Association, 2013)
PURPOSE: The purpose of this study is to evaluate the efficacy and toxicity of oxaliplatin, leucovorin, and 5-fluorouracil (FOLFOX-4) chemotherapy in heavily pretreated patients with recurrent epithelial ovarian cancer (EOC). MATERIALS AND METHODS: Clinical data were reviewed in 28 patients who received FOLFOX-4 as more than the second-line chemotherapy, consisting of 85 mg/m(2) of oxaliplatin as a 2-hour infusion, 200 mg/m(2) of leucovorin as a 2-hour infusion, and bolus 400 mg/m(2) on day 1, followed by a 22-hour infusion of 600 mg/m(2) of 5-fluorouracil for two consecutive days every three weeks. In addition, its efficacy and toxicity were compared with those reported in in three previous relevant studies. RESULTS: A total of 128 cycles of FOLFOX-4 were administered with the median number of five cycles (range, 1 to 10 cycles). In nine patients with measurable disease, complete response (CR) and partial response (PR) were observed in 0 (0%) and two (22.2%) patients, whereas in 19 patients with non-measurable disease, CR and PR were observed in 0 (0%) and five (26.3%) patients. Among all patients, grade 3 anemia, neutropenia, and thrombocytopenia were observed in two (7.1%), three (10.7%), and one (3.6%) patient, and grade 3 fatigue, nausea and vomiting, and peripheral neuropathy were observed in one (3.6%), two (7.1%), and three (10.7%) patients. In addition, median values of time to progressive disease and chemotherapy-specific survival were three months (range, 0 to 10 months) and nine months (range, 4 to 24 months). CONCLUSION: FOLFOX-4 is feasible as salvage chemotherapy with acceptable toxicity for heavily pretreated patients with recurrent EOC.